2010
DOI: 10.1242/jcs.067306
|View full text |Cite
|
Sign up to set email alerts
|

Role of progerin-induced telomere dysfunction in HGPS premature cellular senescence

Abstract: SummaryHutchinson-Gilford Progeria Syndrome (HGPS) is a premature-aging syndrome caused by a dominant mutation in the gene encoding lamin A, which leads to an aberrantly spliced and processed protein termed progerin. Previous studies have shown that progerin induces early senescence associated with increased DNA-damage signaling and that telomerase extends HGPS cellular lifespan. We demonstrate that telomerase extends HGPS cellular lifespan by decreasing progerin-induced DNA-damage signaling and activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
148
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(165 citation statements)
references
References 65 publications
8
148
1
3
Order By: Relevance
“…We are unable to provide an explanation for this. A recent study reports that ectopic telomerase expression prevents progerin-induced proliferative defects, progerin-induced premature senescence, and progerin-induced DNA damage (49), consistent with previous reports (34,50). Telomerase, however, was unable to rescue two other progerininduced defects, namely, repression of the heterochromatic marker H3K27me3 and nuclear abnormalities.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…We are unable to provide an explanation for this. A recent study reports that ectopic telomerase expression prevents progerin-induced proliferative defects, progerin-induced premature senescence, and progerin-induced DNA damage (49), consistent with previous reports (34,50). Telomerase, however, was unable to rescue two other progerininduced defects, namely, repression of the heterochromatic marker H3K27me3 and nuclear abnormalities.…”
Section: Discussionsupporting
confidence: 87%
“…While our findings suggest that telomere integrity is maintained in HGPS cells, other laboratories have reported that DNA damage occurs at telomeres during normal cellular senescence and during progerin-induced premature senescence (34,35). These findings are based on the presence of telomere aggregates that are associated with the nuclear lamina and with ␥H2AX foci.…”
Section: Resultscontrasting
confidence: 40%
See 2 more Smart Citations
“…Impaired proliferation, increased senescence, and telomereassociated DNA damage that is rescued by hTERT have also been shown in cells expressing progerin, the truncated form of LMNA, which causes the premature aging syndrome HGPS (Kudlow et al, 2008;Benson et al, 2010). It remains unclear how increased LMNB1 expression or progerin independently results in growth arrest and cellular senescence.…”
Section: Sa--gal Stainingmentioning
confidence: 99%